O efeito do brand relationship quality na satisfação e lealdade dos consumidores de artigos esportivos - Lira, Allan Carreiro de (Universidade Federal Rural do Semi-Árido, 2020)
The present study sought to analyze the relationship between the quality of the relationship with the brand, satisfaction and loyalty to the sporting goods brand by its consumers, through the conceptual model of the Brand Relationship Quality - BRQ developed by Francisco- Maffezzolli et al (2013 ). The universe of research studied was all people who practice some type of physical activity and who buy sports materials for this practice. Data collection took place through an electronic form hosted on Google Drive and in person in the city of Mossoró in the interior of the state of Rio Grande do Norte. The sample of this research consisted of 303 valid respondents. For the data analysis, two statistical software were used, SPSS Statistic and WarpPLS. To verify the significance of the results obtained, the method of structural equation analysis was used with a focus on modeling of structural equations (Structural Equation Modeling -SEM) of partial least squares - PLS, called PLS-SEM. From the hypothesis checks, it was possible to identify, in this research, the existence of a positive relationship of the relationship with the brand in the face of loyalty and consumer satisfaction and a positive relationship of satisfaction in the face of consumer loyalty in the studied market.
Monografia
Keywords: Lealdade; Satisfação; Relacionamento com a marca; Relação; Loyalty; Satisfaction; Relationship with the brand; Relationship; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO